Learning of Islamic Religious Education in Covid-19 Period: Analysis of Problems and Solutions for Parents - Rahmat Akmal; Mahyudin Ritonga (Universitas Muhammadiyah Makassar, 2020)
Parents are the main hope in the continuity of children's education in covid-19, because teachers in each school only give instruction to students according to the platform used, the position of parents as educators is actually in accordance with the family function in Islamic education namely al-usrah madrasah al-ula, but in reality parents as educators at the time of covid-19 are faced with various problems. This research aims to describe the problems that parents face in online learning as well as solutions that can be pursued. The method used in this study is qualitative, the main source of research is the status of parents in SMP Negeri 3 Lintau Buo North Tanah Datar they pour on social media such as fb, IG and twitter as well as their complaints on whatsApp group that researchers themselves are in the group, data analyzed with the approach of content analysis. The results of the study are parents faced with economic problems, inability to run the profession as teachers, not understanding with materials, lack of understanding of teacher instruction, the use of less professional gadgets. In line with that, researchers offer solutions in the form of cooperation with neighbors in economic-related problems, parents can build communication with the surrounding environment to recruit human resources who can teach privately, multiply communication with people who better understand the content and instruction provided by teachers.